Effectiviness of Disaster Education in Early Childhood Education in Magelang Regency - Siti Azizah Rahmawati (Prosiding University Research Colloquium, 2021)
The study aims to know the application of Disaster Education at the institutions studiesespecially in disaster prone areas. The type of research take a descriptive qualitativestudy through observation, interviews and analizing document as a method of collectingdata. The collected data were analyzed using Miles and Huberman techniques, throughdata reduction, display data, and a deduction. The Research took place in RA muslimatnu 1 wonolelo village sawangan district magelang regency. This research took this placedue to has a high risk of Merapi volcanoes that range 5-7 km to the summit of theflaming mountain. The results of the Research indicates: 1) the mechanism of thedisaster education management in ra muslimat nu 1 wonolelo hasn't been carried out inaccordance with the disaster educational guidelines. The institution has not establishedthemselves as one of the disaster education developers in the curriculum. 2) the materialof disaster education presented is a set of points that are considered important, whilehandling children's reactions was only by giving understanding and giving children asense of secure. 3) the implementation of the integration Disaster Education in thecurriculum and learning plan documents as well as an assessment of Disaster Educationhad not been carried out. 4) The inhibiting factors for the implementation of disastereducation include learning media is still a bit . The effectiveness of disaster educationhas not been carried out effectively, but in this research indicates that the institution hasbeen an effort to apply disaster education in every learning activities.